Qualidade de vida e meio ambiente:: experiência de consolidação de indicadores de sustentabilidade em espaço urbano - Silva, Antonio Sergio da; Souza, José Gilberto de; Leal, Antonio Cezar (Sustainability in Debate, 2013)
The use of indicators for diagnosing the reality of urban spaces has been a trend, given that inequities are materialized in the distribution of social, economic or environmental resources. This study aimed at developing a system of environmental quality and urban life indicators, our empirical focus is on the urban area of Formosa in the State of Goias in Brazil. From the analysis of the factors that underlie experiences in building social and environmental indicators, we sought to identify urban elements that portray the environmental, social, economic, cultural and political sustainability with the participation of local social actors. The development of a system of indicators of quality of environment and urban life with local collaborative networks and portraying the dimensions of sustainability reveals a pedagogical path for the endogenous construction of possibilities of understanding and evaluating key aspects of the production of urban spaces. We consider the possibility of measuring social exclusion and social and environmental segregation from the imbalance between the dimensions of sustainability, translated into elements that combine aspects in the environmental, social, economic, cultural and political dimension.